Association between myelofibrosis and thromboembolism: A population‐based retrospective cohort study. (27th February 2020) - Saliba, Walid; Mishchenko, Elena; Cohen, Shai; Rennert, Gad; Preis, Meir
Abstract: Background: The risk of thromboembolism in myelofibrosis remains incompletely understood. Objectives: To examine the association between myelofibrosis and each of venous and arterial thromboembolism. Methods: A cohort of 1 469 790 adults without a diagnosis of myelofibrosis was identified on 1 January 2007, from the electronic medical records of the largest health‐care provider in Israel. Participants were followed until 31 December 2016 for the occurrence of myelofibrosis. Four randomly selected controls (without myelofibrosis) were matched to each case of myelofibrosis on age, sex, religious identification, and index date. The two groups were followed from the index date until 31 December 2017 for the occurrence of venous and arterial thromboembolism. Results: The study included 642 patients with myelofibrosis and 2568 matched controls. Myelofibrosis was independently associated with increased risk of venous thromboembolism but not with arterial thromboembolism. The propensity score adjusted hazard ratios (HRs) were 6.88 (95% confidence interval [CI], 2.02‐23.45) for venous thromboembolism, and 0.94 (0.49‐1.77) for arterial thromboembolism. Atypical sites of venous thromboembolism occurred almost exclusively in patients with myelofibrosis (four events of Budd Chiari versus none, and two mesenteric vein thrombosis events versus one) and were more likely to occur around the time of myelofibrosis diagnosis. No significant association was found between JAK2 inhibitor treatment (ruxolitinib) and the risk of venous HR 0.97 (0.30‐3.12) or arterial thromboembolism 1.68 (0.78‐3.62). Conclusions: Myelofibrosis is associated with increased risk of venous thromboembolism but not of arterial thromboembolism. Atypical sites of venous thromboembolism are more frequent in myelofibrosis and are more likely to occur shortly after diagnosis.